Jejunal mucosal abnormalities in patients with recurrent aphthous ulceration. Issue 6000 (3rd January 1976) - Ferguson, R; Basu, M K; Asquith, P; Cooke, W T
Abstract : Jejunal biopsies in 33 patients with troublesome recurrent aphthous ulceration seen over one year showed eight with flat mucosa compatible with coeliac disease. All remitted completely on a gluten-free diet, both clinically and haematologically, and the aphthous ulceration did not recur. Gluten sensitivity is aetiologically important in patients with recurrent aphthous ulceration and flat mucosa, and patients with recurrent ulceration should undergo jejunal biopsy.